Erucin exhibits vasorelaxing effects and antihypertensive activity by H2S‐releasing properties. (15th April 2019) - Martelli, Alma; Piragine, Eugenia; Citi, Valentina; Testai, Lara; Pagnotta, Eleonora; Ugolini, Luisa; Lazzeri, Luca; Di Cesare Mannelli, Lorenzo; Manzo, Onorina Laura; Bucci, Mariarosaria; Ghelardini, Carla; Breschi, Maria Cristina; et al.
Abstract : Background and Purpose: Hydrogen sulfide (H2 S)‐releasing agents are viewed as potential antihypertensive drugs. Recently, natural isothiocyanates emerged as original H2 S‐donor agents. Among them, erucin, present in some edible cruciferous plants, shows suitable H2 S‐releasing properties and features of "druggability." The aim of this work was to investigate the erucin‐mediated release of H2 S inside vascular cells, its vasorelaxing effects, and activity on BP of normo and hypertensive animals. Experimental Approach: Intracellular H2 S‐release and the hyperpolarizing effect of erucin were tested using fluorescent dye, in human aortic smooth muscle cells (HASMCs). Its direct vasorelaxing effect and ability to inhibit noradrenaline‐induced vasoconstriction were evaluated on endothelium‐intact or ‐denuded rat aortic rings. Its vasodilator properties were tested in coronary arteries using Langendorff‐perfused rat hearts. Finally, erucin's antihypertensive activity was evaluated in vivo in normotensive and spontaneously hypertensive rats (SHRs) by recording systolic BP using the tail‐cuff method. Key Results: Erucin induced the release of H2 S inside HASMCs. Moreover, erucin hyperpolarized the membrane of HASMCs membrane in a concentration‐dependent manner. It induced vasodilatation of rat aortic rings, in endothelium‐denuded vessels. This effect was further improved by the presence of endothelial NO. When pre‐incubated with rat aortic rings, erucin induced concentration‐dependent inhibition of noradrenaline‐induced vasoconstriction. Erucin did not affect basal coronary flow but restored the flow to normal in pre‐contracted coronary vessels. Finally, in vivo, erucin decreased systolic BP in SHRs by about 25%, and restored the BP to values observed in normotensive rats. Conclusions and Implications: Erucin is an H2 S donor endowed with vasorelaxing and antihypertensive effects. Linked Articles: This article is part of a themed section on Hydrogen Sulfide in Biology & Medicine. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.4/issuetoc